Gradual of opposition of verbs (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The concept of the gradual opposition in linguistics, projected on a verb, is described in the article; a concept "supporting(cored) word" is certain; it is described gradual synonymous rows, it is considered gradual synonymous oppositions; it is placed on the gradual scale of verbs of broadcasting, emotional relation, actually actions.
Keywords: gradual opposition; supporting word; gradual synonymous rows; gradual antonymous rows; gradual scale; verbs of broadcasting; verb of emotional relation; verb of the emotional state; verb of actually actions